A MYKITS – Kernel integration tool for spreadsheet: A feasibility study in Kolej Poly-Tech MARA Ipoh - Rahim, Norafni @ Farlina; Abdul Rahim, Muhammad Syafiq Imran; Mamat, Mohamad Zulhusni (Jurnal Evolusi, 2024)
The utilization of technology in students information management is no longer a vision, but a necessity to every higher education provider. One of the vital students information management is the marks management. Current practice in Kolej Poly-Tech MARA is dual manual entry of marks to two different platform; SPMP and MDR. This reduces productivity of the teaching staff as it time consuming and prone to error. Due to this problem, MyKITS is created to integrate between these two platforms so that the error can be minimized. This study is the feasibility of using MyKITS among the teaching staff in KPTM Ipoh in academic session November 2023. The findings from the thematic analysis based on the experiences of usage found that the use of MyKITS in marks management is efficient, time saving and reduce the error. This study is important to proceed the innovation for pilot study of field study and bigger sample to test the effectiveness of MyKITS